La pieza de Franz, a musical film (Revista Argentina de Musicología, 2018)
This article focuses on the problem of the crossing of languages in 20th-century music. From the analysis case of the Argentine film La pieza de Franz ( 1973), it will be possible to attest the importance of the development of the instrumental theater, regarded as an open space that implies an organic relationship between music, scene, movement, and gesture. Since the 50s. the musical language has been exploring the borders of its own specificity. In the case of Argentina, it was only by the end of the 60s that these experimentations begin to take form, causing an expansion of concepts such as work, originality, and authorship.
Keywords: instrumental theatre; intertextuality; neoavantgarde; musical work; music-film relationships